Violation of Administrative regulations of discretion in employees disciplines: (Raparin Journal of Humanities (RJH), 2024)
The deviation of administrative regulation authority is undoubtedly considered as one of the most audacious fault that may occur to the resolution of disciplinary rules, that taken the fact in account that this undersupply is unlike other violations. Two aspects govern the validity of the disciplinary sanctions, the first is objective that represented by the necessity of sanction (penalty) must be provided for by the law, and clearly determined by the law; whereof, the disciplinary authority must stick to limits of the provision law that imposes penalty in terms of its amount, type and scope. The second aspect is the procedural party that entails that the penalty must be inflicted by legally competent authority. It is sometimes observed that the administration may deviate of its ruling authority in imposing disciplinary penalty, whether by hardening or abusing administration regulations. This research plot explores purpose or deviation in manipulated power use in room of disciplinary sanction as well as elimination of the disciplinary administrative resolution.